2017
DOI: 10.15406/aovs.2017.07.00208
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Changes in Correlation with Corneal Thickness after Phacoemulsification among Diabetic Patients

Abstract: Submit Manuscript | http://medcraveonline.com MethodsWe prospectively examined 23 eyes of each group of patients who were scheduled to have phacoemulsification surgery. Materials were collected from December 2016 till April 2017. Exclusion criteria were a history of previous ocular surgery or inflammation, abnormal findings by slit-lamp biomicroscopic examination, a small pupil diameter after a full dilation of less than 4.0 mm, and a preoperative endothelial cell density of less than 1500 cells/mm 2 . One sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Similar results were found in previous studies. Hugod et al [2] and Elbassiouny et al [26] reported that there were no differences in CCT between diabetic and nondiabetic patients after surgery. This is because there is ECD loss after cataract surgery, but this is not sufficient to affect corneal endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in previous studies. Hugod et al [2] and Elbassiouny et al [26] reported that there were no differences in CCT between diabetic and nondiabetic patients after surgery. This is because there is ECD loss after cataract surgery, but this is not sufficient to affect corneal endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that diabetic patients may be more susceptible to corneal complications before and after intraocular surgery [6–26] . According to the reported results, after cataract surgery, the loss of ECD in diabetic patients was 5.95% to 29.07%, compared to 0.88% to 18.18% in healthy individuals [6–17] .…”
Section: Introductionmentioning
confidence: 98%
“…Biến đổi tế bào nội mô sau phẫu thuật. Nghiên cứu của chúng tôi thực hiện khảo sát mật độ và hình thái tế bào nội mô cũng như chiều dày giác mạc bằng máy NIDEK CEM -530 (Nhật), máy tiến hành chụp hình tế bào nội mô ở vị trí trung tâm và cạnh trung tâm, phân tích hình chụp bằng phương pháp center-to-center với sai số 0,5 -5%, như vậy, thoả theo tiêu chuẩn khuyến cáo của các tác giả Binder (1976) [3] và Osama (2017) [8].…”
Section: Kết Quả Và Bàn Luậnunclassified